Effect of Advertising Rates, the Number of Listeners and Companies that Advertise on Revenue Receipts - Fera Triyani; Citra Etika; Heni Verawati (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to analyze the extent to which advertising rates, number of listeners, and number of companies that advertise affect the receipt of advertising revenue in LPP RRI Bandar Lampung. Research Methodology: The data used include advertising rates based on the type of service (ad spots, adlibs, talk shows), the number of radio listeners per month from 2022 to 2024, the number of companies that advertise, and the receipt of advertising revenue during the period. Results: The results showed that the variety of flexible advertising rates, increasing the number of listeners, and increasing the number of companies that advertise significantly contribute to the increase in advertising revenue in LPP RRI Bandar Lampung. Conclusions: The results showed that the advertising tariff strategy implemented by LPP RRI Bandar Lampung succeeded in increasing revenue, supported by an increase in the number of listeners and advertiser confidence. However, a comparison with other radio stations shows that strategies and results may vary depending on different business models, target audiences, and sociocultural contexts. Limitations: This study has limitations on the scope of data that only includes LPP RRI in Bandar Lampung City, so the results cannot be generalized to all regions of Indonesia. In addition, the variables studied are limited and do not include other external factors, such as marketing strategies and economic conditions, which can also affect advertising revenue. Contributions: This study provides an empirical understanding of the factors affecting the receipt of advertising revenue at LPP RRI, especially in the city of Bandar Lampung. The results of this study can serve as a reference for RRI management in formulating strategies to increase advertising revenue through tariff optimization, increasing the number of listeners, and cooperating with more advertising companies.